1997
DOI: 10.1021/jp9632044
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Chemistry of CuZSM-5 Revisited

Abstract: The recently reported interesting behavior of the EPR spin intensity as freshly prepared CuZSM-5 is dehydrated has been confirmed, and the interpretation offered in explanation has been tested by extending the data. Magnetic susceptibility and optical diffuse reflection spectroscopy have been used to show that the anomalous EPR data correspond to changes in symmetry rather than disproportionation of [CuOH] + into Cu + and Cu 2+ Oas H 2 O is removed, as previously suggested. Moreover, the relatively small negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 20 publications
8
70
1
Order By: Relevance
“…The EPR intensity have been proven by many groups to decrease upon dehydration compared to the intensity of the hydrated zeolite [11,28,33,44,54]. The first example of this was seen for Cu-FAU (with 2.2-16 Cu 2+ ions per unit cell), which decreases to approximately 55% of the intensity already after heating at 100-120 °C in vacuum.…”
Section: The Decrease In Epr Signal Intensity During Dehydrationmentioning
confidence: 98%
“…The EPR intensity have been proven by many groups to decrease upon dehydration compared to the intensity of the hydrated zeolite [11,28,33,44,54]. The first example of this was seen for Cu-FAU (with 2.2-16 Cu 2+ ions per unit cell), which decreases to approximately 55% of the intensity already after heating at 100-120 °C in vacuum.…”
Section: The Decrease In Epr Signal Intensity During Dehydrationmentioning
confidence: 98%
“…Finally, we also have looked in some more detail into the possibilities for charge compensation when Cu(II) is coordinated to an oxygen ring containing only one aluminium. It has been suggested 12,[29][30][31] that Cu(II) coordinated in the proximity of only one Al should carry an OH À group as a fifth ligand, to compensate for the local surplus of positive charge. To check this surmise, we performed additional calculations on two clusters with one Al, placed as in clusters E1 and C1 (represented in Fig.…”
Section: Geometry Optimizationsmentioning
confidence: 99%
“…In the literature, it is often suggested that Cu II ions in the vicinity of only 1 Al are coordinated to an extra-lattice OH Ϫ ligand in order to compensate for the local positive charge. [23,70,128,135] To test this hypothesis, additional calculations were performed for clusters with 1 Al, where Cu II is also coordinated to OH Ϫ . The optimized structures show that the Cu II ion is in a planar threefold coordination environment.…”
Section: Ab Initio Studies Of the Siting Of Cu II In Mordenitementioning
confidence: 99%